The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jpcb.0c03039
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Role of Co- and Post-Translational Events in De Novo Protein Biogenesis

Abstract: The relation between co- and post-translational protein folding and aggregation in the cell is poorly understood. Here, we employ a combination of fluorescence anisotropy decays in the frequency domain, fluorescence-detected solubility assays, and NMR spectroscopy to explore the role of the ribosome in protein folding within a biologically relevant context. First, we find that a primary function of the ribosome is to promote cotranslational nascent-protein solubility, thus supporting cotranslational folding ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(79 citation statements)
references
References 117 publications
(304 reference statements)
6
73
0
Order By: Relevance
“…The analogous behavior observed for these mutants in E. coli and correlation of misfolding effects with phylogenetic conservation is consistent with a selective pressure to avoid misfolding in vivo and with growing evidence that kinetic factors affect stable protein expression in cells (Fig. 3K) ( 20, 26, 60, 61 ). The strong dependence of activity on temperature and Zn 2+ concentration present during expression suggests that mutations promoting formation of the inactive state may disrupt co-translational folding ( 20, 62 ).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The analogous behavior observed for these mutants in E. coli and correlation of misfolding effects with phylogenetic conservation is consistent with a selective pressure to avoid misfolding in vivo and with growing evidence that kinetic factors affect stable protein expression in cells (Fig. 3K) ( 20, 26, 60, 61 ). The strong dependence of activity on temperature and Zn 2+ concentration present during expression suggests that mutations promoting formation of the inactive state may disrupt co-translational folding ( 20, 62 ).…”
Section: Discussionsupporting
confidence: 81%
“…These results strongly support the presence of persistent non-equilibrium folding effects ( Fig. 3D) (20,21,23). A second prediction of the misfolding model was also met by our data: PafA variants with WT activity but with different misfolded fractions (i.e., variants falling along the diagonal blue dashed line in Fig.…”
Section: Many Mutations Reduce Catalysis By Altering Foldingsupporting
confidence: 87%
See 2 more Smart Citations
“…While it is possible that the absolute amount of soluble, misfolded protein may decrease in the cellular context they are unlikely to be entirely eliminated, and such a result would not change our molecular explanation for this phenomenon. It has been observed that even when a protein is synthesized by the ribosome in the presence of a chaperone it still populates states that remain soluble and non-functionalthus, vectorial synthesis does not eliminate these subpopulations 66 . Furthermore, the aforementioned studies of the influence of synonymous codons on protein function in cells are consistent with these subpopulations existing in vivo.…”
Section: Discussionmentioning
confidence: 99%